2011
DOI: 10.1111/j.1440-1681.2011.05538.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of mineralocorticoid action in the brain in salt‐sensitive hypertension

Abstract: Summary 1. The mechanisms by which excessive salt causes hypertension involve more than retention of sodium and water by the kidneys and are far from clear. Mineralocorticoids act centrally to increase salt appetite, sympathetic drive and vasopressin release, resulting in hypertension that is prevented by the central infusion of mineralocorticoid receptor (MR) antagonists. The MR has similar affinity for aldo and the glucocorticoids corticosterone or cortisol. Specificity is conferred in transport epithelia by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 80 publications
1
23
0
1
Order By: Relevance
“…In the meantime, the plasma aldosterone level in both SHRs and WKY rats was lower when compared with their respective controls (Fig 3C). It is well documented that the synthesis of aldosterone increases in response to low plasma sodium so that sodium will be retained in the cell [52]. As such, the increase in sodium as in the present study would certainly secrete low aldosterone.…”
Section: Discussionsupporting
confidence: 49%
“…In the meantime, the plasma aldosterone level in both SHRs and WKY rats was lower when compared with their respective controls (Fig 3C). It is well documented that the synthesis of aldosterone increases in response to low plasma sodium so that sodium will be retained in the cell [52]. As such, the increase in sodium as in the present study would certainly secrete low aldosterone.…”
Section: Discussionsupporting
confidence: 49%
“…The Effect of CS-3150 on Renal Injury in DOCA Rats regulation of blood pressure (Oki et al, 2012;Barrett et al, 2013). For example, Rahmouni et al (2002) reported that intracerebroventricular administration of an MR antagonist decreased SBP in DOCA rats with developed hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, salt-sensitive hypertension is mitigated by intracerebroventricular administration of MR antagonists (236, 237). Analogous studies suggest similar aldosterone-specific effects on salt appetite (534). It has therefore been postulated that aldosteroneselective central MR modulate blood pressure and salt appetite.…”
Section: Central Regulation Of Blood Pressure and Salt Appetitementioning
confidence: 96%